Inaesthetics and Truth: The Debate between Alain Badiou and Jacques Rancière - Shaw, Devin Zane (Filozofski vestnik, 2007)
In this essay I attempt to defend Badiou's conception of inaesthetics, drawn from the Handbook of Inaesthetics, from the pertinent criticisms of Rancière. In doing so, it is possible to delimit the intra-philosophical effects (truth effects) of artistic events (this combination being the domain of inaesthetics). Badiou can be defended from all of Rancière's objections, save the objection that inaesthetics asserts a 'propriety of art.' However, in granting this objection, it is possible to open a different question regarding Badiou's work: what is the status of Badiou's comments on art outside of the Handbook of Inaesthetics? Through a reading of Le siècle, I show that, for Badiou, the importance of art extends beyond inaesthetics to other domains of thought. Yet Badiou has yet to answer the question of how art and truth relate outside of the domain of inaesthetics.